Metalworking unions in action. Trade Unions International of workers in the metal industries. World federation of trade union. (W.F.T.U.)
Continued by: Metalworkers unions in action (ZO 40825). - German ed.: Gewerkschaftliche Aktionen in der Metallindustrie (ZK 40286). - French ed.: L'Action syndicale dans la métallurgie (ZK 30027).